2019
DOI: 10.1186/s13018-019-1516-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for refracture after plate removal for midshaft clavicle fracture after bone union

Abstract: BackgroundOpen reduction and internal fixation (ORIF) with plates and screws is one of the treatment options for clavicle fractures. However, an additional operation for implant removal after union of the fracture is commonly performed due to a high incidence of hardware irritation. Despite union of the fracture, a subsequent refracture might occur after removal of the implant which requires additional surgeries for fixation. This study aims to determine the risk factors associated with refracture of the clavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
1
20
1
Order By: Relevance
“…Refractures of healed clavicles following plate removal are well-known complications and may be related to conditions other than the status of bone healing, such as female sex and low body mass index. 31 Nevertheless, all of these patients had undergone multiple operations prior to the index surgical procedure. All refractures also occurred in the midshaft area known as the “vascular watershed line” of the clavicular bone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Refractures of healed clavicles following plate removal are well-known complications and may be related to conditions other than the status of bone healing, such as female sex and low body mass index. 31 Nevertheless, all of these patients had undergone multiple operations prior to the index surgical procedure. All refractures also occurred in the midshaft area known as the “vascular watershed line” of the clavicular bone.…”
Section: Discussionmentioning
confidence: 99%
“…The final follow-up examination included measurements of active and passive shoulder range of motion and abduction strength using a spring balance. The presence of scapular dyskinesis was recorded using the simplified dichotomous method described by the working group of Kibler et al 10 , 31 (ie, yes or no, in which yes indicates an abnormal dyskinesis pattern whereas no indicates normal scapular motion). 10 , 31 The clinical functional outcome was also assessed using the Constant score (CS).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the refracture, there are several common risk factors: comminuted fracture pattern and bone defects [32,33], inadequate compression between fractures [32], microfracture occurred during removal of screws or wires [34]. Recently, Tsai et al [35] claimed that female and low BMI were another two risk factors associated with refracture post plate removal for midshaft clavicle fractures. In our study, the female patient suffering from refracture was a slim young woman with a very small bone diameter.…”
Section: Discussionmentioning
confidence: 99%
“…Since the frequency of ORIF increases with clavicle fracture, some studies have reported the issue of implant removal (IR) [11][12][13]. In some cases, IR is inevitable due to infection, nonunion, or implant breakage.…”
Section: Introductionmentioning
confidence: 99%